Hybrid Transvaginal NOTES Nephrectomy: Postoperative Sexual Outcomes. A Three-center Matched Study - ŞENER, TARIK EMRE; TANIDIR, YILÖREN (ELSEVIER SCIENCE INC, 2017)
OBJECTIVE To evaluate our experience in patients undergoing hybrid transvaginal natural orifices transluminal endoscopic surgery (NOTES) nephrectomy and evaluate the sexual functions in the postoperative period. MATERIALS AND METHODS Prospective data of 71 patients with renal tumors who underwent hybrid NOTES radical nephrectomy in three different centers were collected from March 2010 to October 2015. Patient and surgical characteristics were recorded. Sexual function was evaluated using the Female Sexual Function Index questionnaire the day prior to the operation and 3 months after. RESULTS The mean age, tumor size, and operation duration were 66.16 +/- 11.21, 8.51 +/- 3.31 cm, and 119.94 +/- 21.38 minutes, respectively. Five patients were immediately reoperated due to bleeding from uterine veins. The complication risk increases significantly with increasing tumor size. Among the whole cohort, even the Female Sexual Function Index score differences are small; there is a statistically significant decrease in the postoperative period in all domains except sexual satisfaction. In fact, the patients reported unaltered sexual function after surgery and satisfaction with the result when asked directly. In subgroup analyses, in nulliparous patients (n = 60), arousal, sexual desire, orgasm, and satisfaction domains have no significant differences in pre- and postoperative periods. CONCLUSIONS Hybrid NOTES nephrectomy is a feasible, safe operation that can be performed for large renal tumors. Due to incisions in the vaginal wall for specimen retrieval, sexual function can be altered in the postoperative period. So patient selection, preoperative evaluation, and close follow-up are mandatory. With this in mind, we strongly support the use of hybrid transvaginal NOTES nephrectomy for large renal tumors especially in nulliparous patients. (C) 2016 Elsevier Inc.
Keywords: EPIDEMIOLOGY STROBE STATEMENT; DONOR NEPHRECTOMY; VAGINAL DELIVERY; SURGERY; GUIDELINES; LESS